Pengaruh Penerapan Sistem E-Filing, Pengetahuan Perpajakan Dan Peran Relawan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Bekasi - Novianti, Anita; Nuryati, Tutty; Rossa, Elia; Puspaningtyas, Dewi; Manrejo, Sumarno (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Taxes play a critical role in Indonesia's development. According to statistics provided by the Central Bureau, taxes contributed an average of 79% to 82% of total state revenue between 2019 and 2023. However, there remains a discrepancy between the number of taxpayers reporting their obligations and the set target. To enhance compliance, innovations such as the e-filing system and tax volunteer program are utilized. This study employs a quantitative methodology utilizing surveys as a data collection technique through individual taxpayer questionnaires in Bekasi. The population and sample were determined using a simple random sampling methodology. Primary data were gathered from the questionnaires, while secondary data were collected from the literature, forming the basis of the research. The study's findings suggest that the utilization of the e-filing system, possession of tax knowledge, and availability of tax volunteers significantly contribute to the compliance of individual taxpayers in Bekasi.